The Surge: Turning Away from Affect. Issue 3 (August 2018) - Bewes, Timothy
Abstract : This essay offers a critique of the philosophical 'turn to affect', a formation represented here by the work of Brian Massumi and Mark Hansen. In such discourses, affect is celebrated as an entity that is inimical to conceptualisation, subjective intention and linguistic transcription. However, insofar as it boasts such qualities, affect cannot, I argue, be celebrated or made the object of a critical 'turn'. In drawing on Deleuze's work, contemporary scholarly discourses on affect dispense with Deleuze's most profound proposition: of an order of philosophy, perception, reflection and thought that originates outside, or is no longer dependent upon, a human perspective.